Perlindungan Hukum Kepada Tersangka Pada Tahapan Pra Adjudikasi - Juler Orin Tasya Saknohsiwy; Juanrico Alfaromona Sumarezs Titahelu; Julianus Edwin Latupeirissa (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2022)
Various provisions for the implementation of pre-adjudication, investigative procedures and investigations into alleged criminal acts of persecution. This research is a normative juridical research on this problem and then examines and knows the answers to this problem through a concept approach, statutory approach and case approach, then from the results of the description conclusions and suggestions can be drawn. The results of this research and problem analysis use the concept of the rights of suspects who commit crimes, the concept of pre-adjudication, which is an initial framework for thinking about legal protection for suspects at the pre-adjudication stage. The results of the study show that the form of legal protection for suspects at the pre-adjudication stage should be carried out by the suspect's attorney by asking the Southwest Maluku Police Investigators and the Public Prosecutor to carry out integrated (integrated/synchronized) Investigation and Prosecution between Investigators, Public Prosecutors and the Court so that the case is immediately transferred to the Saumlaki District Court to carry out an Examination and obtain a Court Decision and what legal remedies can be taken against violations of the suspect's rights at the pre-adjudication stage can be carried out through pre-trial by the suspect's attorney with based on the legal provisions governing the rights of suspects as protected in the Criminal Procedure Code, namely the suspect or defendant has the right to be immediately examined by investigators, has the right to be immediately submitted to court and has the right to be tried immediately and get a court decision.